The ecology of plants - Gurevitch, Jessica; Scheiner, Samuel M., 1956-; Fox, Gordon A., 1952- (Sinauer Associates/Oxford University Press, 2021)
"The Ecology of Plants presents a comprehensive, engaging, and plant-focused treatment of ecology. Written for undergraduate students taking courses in plant ecology, the text links ecosystem function through an understanding of physiology, ecological theory, and climate change at multiple spatiotemporal scales. It covers subjects unique to plants, such as photosynthesis, soil interactions, and the ecology of plants. This third edition is substantially reorganized to reduce repetition and to bring important conceptual and subject material together that had been scattered in the previous edition. The authors have clarified and updated material throughout and deleted material that is outdated to emphasize newer topics and to shorten the discussion of topics that are still necessary background material but are emphasized less in current thinking in the field. Overall, The Ecology of Plants provides students with fundamental knowledge in plant sciences to address pressing issues ecosystems face in the age of a rapidly changing climate"--